Fatigue and cognitive impairment in neuroborreliosis patients posttreatment—A neuropsychological retrospective cohort study - Anna Helena Sigurdardottir; Fredrikke Christie Knudtzen; Anita Nymark; Malcolm Bang (Brain and Behavior, 2022)
Abstract Background The aim of this study was to determine the prevalence of fatigue and cognitive impairment in patients with neuroborreliosis (NB) posttreatment and to determine whether delayed treatment initiation led to higher levels of fatigue and cognitive impairment. Methods The study population consisted of 88 patients with NB included between October 10, 2014, and August 21, 2020, at the Clinical Center for Emerging and Vector‐borne Infections at Odense University Hospital, Denmark. The Symbol Digit Modalities Test (SDMT) was used as a cognitive screening test, and the Modified Fatigue Impact Scale (MFIS) was used to assess the patients’ level of fatigue over the course of a year. Results Overall, 14.3% of patients had an SDMT score indicative of cognitive impairment, and 38.8% of patients reported experiencing fatigue 12 months posttreatment. We found no statistically significant differences in fatigue or cognitive impairment when comparing the patients who had a treatment delay of ≤14 days and those with a treatment delay of >14 days (p > .05) 12 months posttreatment. A random effects regression model showed a significant positive correlation between longer treatment delay and higher MFIS scores, indicating higher levels of fatigue. Conclusions The results of this study show that both the early and late treatment groups improved significantly over a 12‐month period in terms of both cognitive symptoms and fatigue. However, it also showed that a substantial subgroup of patients with NB still suffer from fatigue and cognitive impairment 12 months posttreatment.